1998
DOI: 10.1159/000052696
|View full text |Cite
|
Sign up to set email alerts
|

Cathemeral Behavior of Eulemur macaco macaco at Ambato Massif, Madagascar

Abstract: A 15-month field study of Eulemur macaco macaco socioecology at Ambato Massif revealed year-round cathemeral activity. There were both daily and seasonal rhythms of diurnal behavior. However, as measured by vocalizations and group movements, the relative occurrence of nocturnal activity was not markedly seasonal and apparently followed the phases of the moon. Increased nocturnal activity was noted when the moon was waxing and during the full moon. These nocturnal activity data are preliminary, as they were gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 22 publications
4
53
0
2
Order By: Relevance
“…Thirdly, Eulemur lack adaptations for acute night vision [15,22,23], therefore during the night, feeding in the moonlit canopy may be easier than in the dark undercanopy. Colquhoun [24] has related the degree of nocturnal activity of black lemurs with the phase of the moon.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, Eulemur lack adaptations for acute night vision [15,22,23], therefore during the night, feeding in the moonlit canopy may be easier than in the dark undercanopy. Colquhoun [24] has related the degree of nocturnal activity of black lemurs with the phase of the moon.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades or so cathemeral behaviour has been reported in all species of Eulemur , including E. fulvus [Meyers, 1988;Tattersall, 1982Tattersall, , 1987Overdorff and Rasmussen, 1995;Borgognini-Tarli, 2002, 2006;Donati et al, 1999Donati et al, , 2001Rasmussen, 1999], Tattersall E. mongoz [Curtis et al, 1999;Curtis and Zaramody, 1999;Rasmussen, 1999], E. macaco [Andrews and Birkinshaw, 1998;Colquhoun, 1998], E. coronatus [Wilson et al, 1989;Freed, 1996], and E. rubriventer [Overdorff, 1988;Overdorff and Rasmussen, 1995]. Cathemeral behaviour has also been clearly documented in at least one species of Hapalemur [Mutschler et al, 1998], and anecdotal evidence suggests that it is probably widespread in this genus [though see Tan, 1999, andMutschler, quoted in Curtis andRasmussen, 2002].…”
Section: Occurrence and Correlates Of Cathemeral Activitymentioning
confidence: 99%
“…At the very least it is clear that among (and even within) the lemur and other primate taxa now considered to be cathemeral there may exist considerable lability in the apportionment of activity through(out) the light and dark parts of the daily cycle. It is also evident that the resulting variation in activity patterns may be controlled or at least infl uenced by a variety of environmental fac-tors including temperature, daylength, rainfall, predation, food resource availability [much debated as an infl uence of this kind: contrast Colquhoun, 1998, and Curtis et al, 1999, with Engqvist and Richard, 1991 and quality [see discussion by Wright, 1999], varying nocturnal light levels, and so forth. It has also been suggested, though to some of us less plausibly, that social factors might also play a role in modulating activity [see, for instance, van Schaik and Kappeler, 1996;Ostner and Kappeler, 1999].…”
Section: Occurrence and Correlates Of Cathemeral Activitymentioning
confidence: 99%
“…Alternatively, extending activity into both the diurnal and nocturnal phase may allow ani-mals to switch to a high-fi bre diet and increase feeding time when food is scarce [Engqvist and Richard, 1991] or exploit temporally limited resources [Sussman and Tattersall, 1976]. In general, there has been little support for a foraging advantage to cathemerality [Colquhoun, 1998;Curtis et al, 1999] and Kappeler and Erkert [2003] concluded that improved food availability is not the primary proximate or ultimate determinant of cathemeral activity. It is important to remember, however, that patterns of diet choice and diet composition can be complex to analyse, particularly when species composition and intake rates are so diffi cult to observe during the nocturnal phase, and diet selection may also be confounded by factors such as predation risk or interspecifi c competition.…”
Section: Predictionmentioning
confidence: 99%